THE CRIB II (CLINICAL RISK INDEX FOR BABIES II) SCORE IN PREDICTION OF NEONATAL MORTALITY - Orhideja Stomnaroska; Dragan Danilovski (Macedonian Academy of Sciences and Arts / Sciendo, 2020)
Predicting the outcome of neonatal critical patients remains elusive. The multiple factors of maternal state of health (infections, diabetes, gestosis), the placental situation (premature rupture of membranes) as well as multiple factors from the baby (small for gestational age, low Apgar score, low birth infections, mechanical ventilation, hypoglycaemia hyperglycamiea) render the approach to treatment of each patient individual and the outcome uncertain. Several approaches and scales are developed in order to assess the mortality risk in those rather complicated situations. We used the CRIB-II scale to assess the mortality risk in 80 patients delivered in a large tertiary level hospital with more than 4,000 deliveries yearly. The patients were stratified according to all the neonatal risk factors and comorbidities. The CRIB-II scale identified well the mortality rates, but not the outcomes. A large and well-balanced cohort of patients followed for a longer period is required to discern in detail the importance of CRIB-II scale in predicting outcomes in high-risk new-borns. This could serve as an assistance to personalized approach to severely sick children. In addition, it is a valuable method in comparing outcomes in different NICUs and outcomes in different times in the same NICU, thus rendering possible improvements in the same unit and among several NICU departments.
Keywords: neonatal mortality; high-risk babies; CRIB-II score